Molecular Evolution of Metallothioneins of Antarctic Fish: A Physiological Adaptation to Peculiar Seawater Chemical Characteristics - Rigers Bakiu; Francesco Boldrin; Sara Pacchini; Sophia Schumann; Elisabetta Piva; Anna Maria Tolomeo; Diana Ferro; Alessandro Grapputo; Gianfranco Santovito; Paola Irato (Journal of Marine Science and Engineering, 2022)
Metallothioneins (MTs) are low-molecular weight sulfur-rich proteins, widely distributed in nature. They play a homeostatic role in the control and detoxification of metal ions. Previous studies indicated that MTs also have the capacity to scavenge reactive oxygen species. This study aimed to investigate the evolution of the protein in the notothenioid fish, evolved under the selective pressure of relatively high oxygen partial pressures, characteristics of cold Antarctic seawaters, and relatively high concentrations of metal ions, Cd and Cu in particular. The cDNA sequences of MT isoforms were characterized in members of the Nototheniidae, Bathydraconidae, Artedidraconidae, and Channichthyidae families. The phylogenetic relationships of MTs from these families and other teleosts were inferred by using Maximum Likelihood and Bayesian methods. The analysis of coding region and untranslated (UTR) sequences indicated the presence of two MT clades, each containing one of the two MT isoforms, MT-1 and MT-2. Our results indicated, for the first time for these proteins, that the evolution of MT genes has been characterized by strong purifying selection, whereas it did not observe any evidence of positive selection. In addition, phylogenetic analysis of the UTRs suggested that functional changes, in particular related to the MT-1 gene expression, had accompanied the duplication event.